Exploring Students’ Perceptions of Outdoor Biology Learning Activities in Botanical Garden - Asyah Dwi Hastika; Saefudin; Bambang Supriatno (Postgraduate, University of Mataram, 2024)
Outdoor learning has become a relevant learning method to enrich students' learning experience in biology. Botanical gardens, as places that reflect biodiversity, offer unique potential for integrating outdoor learning. This study aims to describe students' perceptions of outdoor learning that has been carried out in the botanical garden as well as the potential and barriers. This research method is a case study. Data collection techniques were questionnaires, structured and semi-structured interviews. The sampling technique used was convenience sampling with a sample of 32 class x students at one of the high schools in Bandung. Responses were expressed in perception numeric index to quantitatively reveal the perceptions of grade 10 students towards the outdoor learning experience that has been carried out. The results revealed that out of 32 respondents, most students showed positive perceptions towards outdoor learning in the botanical garden with a mean index = 55.23 (range 42.5-65.0) with standard deviation (sd) = 6.0. This perspective is influenced by the potential and obstacles in the implementation of outdoor learning conducted in botanical gardens. The implications of this study open up opportunities to design learning strategies that are more effective and can be applied by teachers in organizing biology learning at the high school level.